Evaluation of impulsivity and complex attention functions of subjects with substance use: Sample from adiyaman province - Ali Kustepe; Aysun Kalenderoglu; Mustafa Celik; Esra Kaya Bozkurt; Mehmet Hamdi Orum; Sukru Uguz (Medicine Science, 2019)
The aim of this research is to compare impulsivity and complex attention functions in individuals with substance use disorders to those who do not use substance. Design of this study was a case-control study. Universe of this study was patients with substance use who admitted to psychiatry department of our hospital. Among them, 33 (94.3%) males and 2 females between 18-65 years of age formed the study sample. Randomly selected 23 (92.0%) males and 2 (8%) females without any substance use disorders who were similar to the study group according to age and sex formed the control group. A statistically significant difference was found between the two groups in terms of Barratts total impulsivity score, motor impulsivity, and non-plan point scores (p˂0.05). There were two statistically significant differences (p˂0.05) between two groups in terms of Trail Making Part B, Trail Making Part B / Trail Making Part A, Trail Making Part B - Trail Making Part A, Trail Making Part B + Trail Making Part A. Subjects using substances have difficulties with concentration, delaying gratification, making appropriate decisions, and inhibiting responses. Another important finding of this study was higher levels of disturbance in complex attention function in subjects with substance use. According to this result, subjects with substance use have difficulties in changing between different stimulating sets, following consecutive stimuli and mental flexibility. Long term follow-up studies are needed to understand the reciprocal relations between substance use, impulsivity, and complex attention. [Med-Science 2019; 8(1.000): 67-71]